Sustainable Concrete Bricks Partially Comprised of Supplementary Cementitious Material and Alternative Fine Aggregate- A Review - ABDUL MUHAIMIN BIN ABU BAKAR (Progress in Engineering Application and Technology, 2021)
T he usage of cement and normal fine aggregates, sand is tended to givepollution to this world. Researchers finds that there are many materials or substancesthat can replace them. Most of the materials are waste materials and non-pollutionmaterials. The potential of using this material of alternative fine aggregates andsupplementary cementitious materials will produce more sustainable concrete bricksin the future. In this paper, an optimum percentage of partial fine aggregates andsupplementary cementitious materials of the sustainable concrete bricks will beobserved. Then the mechanical properties such as compressive strength and waterabsorption of the sustainable conrete bricks will be compared. This will help otherresearchers and construction industry to produce more eco-friendly brick that canperform as conventional bricks.